Shaping resilient higher education institutions through business continuity management / Ameer Haider Ali, Nor Azilah Husin and Mokhtar Abdullah - Ali, Ameer Haider; Husin, Nor Azilah; Abdullah, Mokhtar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Business Continuity Management (BCM) is the emergent organizational resilience and risk alleviating standard and is deemed necessary for competitive advantage. This study looked at exigency approaches (contingency) and risk management practices as covert causes which can contribute towards improved business continuity planning (BCP) and business continuity management (BCM), both, resulting in higher levels of university resilience. This quantitative research study adapted and adopted from an exploratory model to examine the factors influencing the practice of Business Continuity Planning (BCP) and Business Continuity Management (BCM) at higher educational institutions (HEIs). Survey responses were collected from 100 universities across 10 countries on four continents. Respondents comprised academic managers and academicians, including staff positions, personnel who are in-charge of operations and planning. The analyses showed strong evidence that contingency approaches and risk management together, have significant relationships with BCP and eventual BCM, thus impacting HEIs resilience. Even though risk management and contingency approaches have a significant impact on BCP, they do not have a significant influence on university resilience. Social, economic and developmental benefits are cited in the discussions section to strengthen the practice of BCM at HEIs.